Exploring the Impact of Transformational Leadership on Employee Performance: Insights into Organizational Effectiveness and Leadership Behavior - Gumelar Hamdan; Charles Edward; Zephaniah Kristianir (IHSA Institute, 2024)
This research explores the relationship between transformational leadership and employee performance within organizational contexts. Through a mixed-methods approach incorporating quantitative surveys and qualitative interviews, the study investigates the impact of transformational leadership behaviors on various dimensions of employee performance, including task performance, contextual performance, and adaptive performance. The findings reveal a significant positive association between transformational leadership and employee performance, with leaders who exhibit visionary, inspirational, and empowering behaviors fostering a culture of excellence and innovation wherein employees thrive and contribute their best efforts towards achieving shared goals. The study's results align with existing literature and theories on transformational leadership, providing empirical support for theoretical constructs such as the Full Range of Leadership Model and the Social Exchange Theory. Moreover, the implications of the findings extend beyond theoretical insights to practical implications for organizational leaders and practitioners, highlighting the importance of aligning leadership practices with organizational values and goals to maximize their impact on performance outcomes. Ultimately, the research underscores the transformative power of transformational leadership in driving organizational effectiveness and success in today's dynamic business environment.